Changes in Labour Market, Job Creation and Job Destruction from the Change of Regime till Nowadays - Tóthné Sikora, Gizella (Theory, Methodology, Practice – Review of Business and Management, 2005)
I analyse the confirmation of Hungarian labour market process and the characteristics of workforce mobility and flexibility in my paper. Workforce mobility is influenced by privatisation and the changes in the property structures. In my paper I deal with the coherence between globalisation and relocation, the geographical resettlement of workplaces and the foreign companies that provide job to 35% of the employees. In the next section of my paper I examine the structure of employment, using the job creation and destruction rates, the relative changes in the weights of employment sectors and the development in the market evaluation of workgroups of different age and qualification. The conclusion is that the result of efficient capital – efficient knowledge copulation raises the value of knowledge which is mainly the increment of young and high qualified workforce.